A Therapeutic Challenge: Liddle's Syndrome Managed with Amiloride during Pregnancy. (25th August 2014) - Caretto, Amelia; Primerano, Liviana; Novara, Francesca; Zuffardi, Orsetta; Genovese, Stefano; Rondinelli, Maurizio
Abstract : Liddle's syndrome (LS) is a rare heritable form of hypertension that often affects young patients. It is caused by gain-of-function mutations of the kidney epithelial sodium channel (ENaC) and it is classically associated with hypokalemia and suppression of renin and aldosterone. LS is characterized by responsiveness to ENaC inhibitors but not to mineralocorticoid receptor inhibitors. Consequently the most effective treatment is amiloride. This drug is not used in pregnancy, as it has not been sufficiently studied during gestation. However for pregnant LS patient amiloride is the most effective drug in decreasing blood pressure. Herein we report the case of a LS patient, who has been followed up by a multidisciplinary teamwork during her first pregnancy. Hypertension worsened after the 25th week of gestation and amiloride was safely administered, firstly in combination with hydrochlorothiazide (the only formulation commercially available in Italy) and, thereafter, as a single drug. Genetic testing was performed in the patient's family in order to support diagnosis and clinical management.